Rooster Cogburn - Stuart Millar; Zerbe, Anthony, 1936-; John McIntire; Katharine Hepburn; Paul Koslo; Richard Jordan; Richard Romancito; John Wayne (USA Universal Pictures, 1975)
A small village in the Indian Nation that is run by a Minister Goodnight and his daughter Eula is overrun by a band of drunken thugs. They kill and rape the people of the village. Miss Goodnight then teams up with the ruthless Marshal Rooster J. Cogburn who goes after them and bring them to justice.
Marshal Rooster Cogburn unwillingly teams up with minister's daughter Eula Goodnight to track down the killers of her father.
Martha Hyer
Language(s): English, French, Italian, Spanish
Subtitle(s): English, French, Italian, Spanish, Portoguese, Hebrew, Arabic, Russian, Turkish, Greek
Keywords: Comedy; Western